PENGARUH KOMUNIKASI ANTAR PRIBADI DAN KUALITAS PRODUK TERHADAP MOTIVASI KERJA (Studi Kasus pada Multi Level Marketing Perusahaan Tianshi) - Dwi Kusuma Yuniarti (Professional: Jurnal Komunikasi dan Administrasi Publik, 2014)
The rise of the networked enterprises, including the company Tianshi has made more than 4 million Indonesian listed as direct sales distributor. In doing this sale, face to face communication was very effective to changed attitudes, opinions and behavior of a person. This study was a quantitative and it had three variables: Variable X1 was interpersonal communication, Variable X2 was a quality product, and variable Y was the motivation to work. From the research, it’s known that the knowledge of the quality and benefits of a product would encourage other people (potential consumers) to buy a product. From the research, it could be concluded that there was a significant influence of interpersonal communication sponsor on the motivation to work among network members. This was due to the good relationship between sponsors and their members. Sponsors who were able to create a pleasant atmosphere as well as deliver interesting messages to the members would make the members understand any information submittedKeywords: networked enterprises, interpersonal communication, working motivation, product quality